Noncyclical and cyclical mastalgia in Turkish women: Prevalence, risk factors, health-care seeking and quality of life. Issue 1 (4th March 2022) - Bolat, Hacı; Aşcı, Özlem; Kocaöz, Servet; Kocaöz, Semra
Abstract: Our aim in this study was to determine the prevalence of cyclical and noncyclical mastalgia, its underlying risk factors, and to examine its effect on women's quality of life. This study was conducted on 415 women, among whom the prevalence of mastalgia was found as 20.7%. It was found that experiencing intense stress, daily coffee and chocolate consumption, breast surgery history and the menstruation pattern were risk factors associated with mastalgia. Some domains of quality of life were found to be negatively affected in women who had mastalgia. Awareness among women about the risk factors of mastodynia and lifestyle changes is needed to improve mastalgia management.